2015
DOI: 10.1073/pnas.1418088112
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin distribution in lipid rafts of artificial monolayer membranes visualized by Raman microscopy

Abstract: Sphingomyelin (SM) and cholesterol (chol)-rich domains in cell membranes, called lipid rafts, are thought to have important biological functions related to membrane signaling and protein trafficking. To visualize the distribution of SM in lipid rafts by means of Raman microscopy, we designed and synthesized an SM analog tagged with a Raman-active diyne moiety (diyne-SM). Diyne-SM showed a strong peak in a Raman silent region that is free of interference from intrinsic vibrational modes of lipids and did not ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
103
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 43 publications
0
103
0
Order By: Relevance
“…44,45 Such bio-orthogonal chemical imaging offers a powerful platform for functional metabolic imaging in live cells and animals. 4655 Its success underscores the importance of introducing vibrational probes to improve specificity and sensitivity of nonlinear Raman microscopy. However, even with extensive efforts of instrumentation improvement and small-tag optimization, the detection sensitivity of SRS is still in the range of 35 μM (i.e., diyne tags, double-conjugated alkynes) 51 to 200 μM (small alkyne tags).…”
mentioning
confidence: 99%
“…44,45 Such bio-orthogonal chemical imaging offers a powerful platform for functional metabolic imaging in live cells and animals. 4655 Its success underscores the importance of introducing vibrational probes to improve specificity and sensitivity of nonlinear Raman microscopy. However, even with extensive efforts of instrumentation improvement and small-tag optimization, the detection sensitivity of SRS is still in the range of 35 μM (i.e., diyne tags, double-conjugated alkynes) 51 to 200 μM (small alkyne tags).…”
mentioning
confidence: 99%
“…The conjugated triple bonds in diyne-SM 2 show a significantly enhanced intensity and peak shifts to longer wavenumber at 2263 cm À1 , leading to an approximately five-fold greater peak height than that of the alkyne in 1; the Raman imaging of the distribution of 2 in phase-separated membranes has been published. 12 In the case of SM-d 9 3, the observed peaks can be assigned to symmetric CD 3 stretching at 2184 cm À1 , and Fermi resonance multiplets at 2132 cm À1 and 2081 cm À1 with overtone or combination tone of CD 3 deformation. 18 A peak due to asymmetric CD 3 stretching at $2276 cm À1 was unnoticeable owing to the overlap with rotation-vibrational Raman modes of nitrogen in air around 2332 cm À1 .…”
Section: Resultsmentioning
confidence: 95%
“…9,10 Initially, we attempted to introduce the conjugated diyne moiety using 3-bromoprop-2-yn-1-ol as the coupling partner under the classical CadiotChodkiewicz coupling conditions (copper(I) chloride, 5 mol %; hydroxylamine, 30 mol %; i-PrNH 2 in aqueous methanol), 11 as reported separately. 12 Unfortunately, it was difficult to drive the coupling to completion and only a modest conversion was achieved, as judged by 1 H NMR. Furthermore, the remaining alkyne 1 was hardly separable from compound 2 due to their similar polarities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids are a class of bioactive lipids found in cell membranes that modulate the biophysical properties of biological membranes (1) and exert a critical role in signal transduction (2,3). Multiple studies in the last decades revealed that sphingolipids control critical cellular functions such as cell cycle, senescence, apoptosis, cell migration and inflammation (4).…”
Section: Introductionmentioning
confidence: 99%